Development of Recombinant Immunoblot Assay Diagnostic Test Based on HIV-1 in Indonesia - Jeanne Elvia Christian; Silvia Tri Widyaningtyas; Budiman Bela (Cell and BioPharmaceutical Institute, 2022)
Background: High mutation rates in HIV-1 could affect the accuracy of diagnostic tests. Therefore, recombinant antigen that has an immunodominant and conserved region from HIV-1 need to be developed to detect HIV-1 infection in Indonesia.Materials and methods: The recombinant antigens comprise of Gag (p24), Pol and Env (gp41). Each antigens was expressed in the Escherichia coli expression system and purified using Ni-NTA chromatography. The reactivity of purified antigen against HIV antibodies was tested against a group of 50 HIV-positive plasma samples and 45 HIV-negative plasma samples in a recombinant immunoblot assay (RIBA) platform test. Moreover, 21 of 50 HIV-positive samples and 3 of 45 HIV-negative samples were also tested using HIV blot 2.2 to compare RIBA with a commercial western blot kit. Ten HBV-positive and 10 HCV-positive plasma samples were used to check cross-reactivity with HIV recombinant proteins in RIBA.Results: All HIV-positive samples (100%) tested with RIBA were reactive towards Gag (p24), Pol, Env (gp41). Otherwise, 3 of 21 HIV-positive samples assayed with HIV blot 2.2 were not reactive to Pol protein. All HIV-negative samples tested with RIBA and 3 HIV-negative samples tested with HIV blot 2.2 did not produce any bands of HIV antigens. Few HBV and HCV samples showed reactivity towards HIV recombinant proteins.Conclusion: Each recombinant protein, Gag (p24), Pol, Env (gp41), could be expressed and purified, as well as had reactivity to HIV-positive samples in RIBA test. Therefore, RIBA can be used as a diagnostic test to detect HIV-1 infection in Indonesia.Keywords: diagnostic, HIV-1, immunodominant, recombinant immunoblot assay (RIBA)